Overview evidence on interventions for population suicide with an eye to identifying best-supported strategies for LMICs. (12th February 2016) - Fleischmann, A.; Arensman, E.; Berman, A.; Carli, V.; De Leo, D.; Hadlaczky, G.; Howlader, S.; Vijayakumar, L.; Wasserman, D.; Saxena, S.
Abstract : Globally, over 800 000 people died by suicide in 2012 and there are indications that for each adult who died of suicide there were likely to be many more attempting suicide. There are many millions of people every year who are affected by suicide and suicide attempts, taking into consideration the family members, friends, work colleagues and communities, who are bereaved by suicide. In the WHO Mental Health Action Plan 2013–2020, Member States committed themselves to work towards the global target of reducing the suicide rate in countries by 10% by 2020. Hence, the first-ever WHO report on suicide prevention, Preventing suicide: a global imperative, published in September 2014, is a timely call to take action using effective evidence-based interventions. Their relevance for low- and middle-income countries is discussed in this paper, highlighting restricting access to means, responsible media reporting, introducing mental health and alcohol policies, early identification and treatment, training of health workers, and follow-up care and community support following a suicide attempt.